THEORETICAL RESEARCH OF THE POSSIBILITY OF JOINTLESS TRACK ARRANGEMENT IN CURVED SECTIONS OF RADIUS LESS THAN 350 METERS (Transport systems and technologies, 2021)
The traditional structure of the upper structure of the track on the main railways of Ukraine in curved sections with a radius of less than 350 m is a link structure of the track with wooden sleepers. This track design is not rational under current operating conditions. The use of a more advanced jointless track design in curves with a radius of less than 350 m is limited primarily by the condition of ensuring the transverse stability of the rail-sleeper lattice. To be able to expand the use of jointless track construction in curved sections with a radius of less than 350 m, it is necessary to know the values of the transverse forces of interaction of the structures of the upper track structure with the moving carriage. Knowing the forces of interaction, it is possible to estimate by what value the transverse stability of the rail-sleeper lattice will be provided and to make constructive decisions on its increase.The method of determination of transverse horizontal forces of interaction of track and moving carriage in curves of radius less than 350 m taking into account quasi-static compressive forces in a train is given. The reasons for these forces are related to the presence of eccentricity of the autoclutch shank in the horizontal and vertical planes. Theoretical calculations of horizontal transverse forces of interaction are carried out according to the given technique and coefficients of stability of a rail-sleeper lattice in curved sites are defined.The main conclusions concerning the possibility of operation of the jointless track structure in curved sections with a radius of 350 m and less are made.
Keywords: railway track, jointless track construction, small radius curves, transverse stability, horizontal transverse forces.